2022
DOI: 10.1029/2022gl100868
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Ocean Wave Transfer to Ross Ice Shelf Flexure

Abstract: The Ross Ice Shelf (RIS) is the world's largest ice shelf. It is hundreds of meters thick, with width and length many hundreds of kilometers and covering the majority of the Ross Sea bay (Figure 1a). Two sets of seminal experiments have been made on the RIS over the past two decades to measure its vibrational response to ocean surface wave forcing, ranging from swell (roughly frequencies 0.03-0.1 Hz or periods 10-30 s) to infragravity (IG) waves (0.003-0.02 Hz or 50-300 s) to very long period waves including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…In particular, flexural-gravity waves at periods in the swell regime are amplified by crevasses in ice shelves (Bennetts et al. 2022), and, thus, our findings highlight a potential, additional role of water–ice coupling and extensional waves in these amplifications. Further, the thin-plate model presented could be extended to study whether periodic thickness variations in the ice shelf block ocean wave energy propagation through the shelf (Freed-Brown et al.…”
Section: Conclusion and Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In particular, flexural-gravity waves at periods in the swell regime are amplified by crevasses in ice shelves (Bennetts et al. 2022), and, thus, our findings highlight a potential, additional role of water–ice coupling and extensional waves in these amplifications. Further, the thin-plate model presented could be extended to study whether periodic thickness variations in the ice shelf block ocean wave energy propagation through the shelf (Freed-Brown et al.…”
Section: Conclusion and Discussionsupporting
confidence: 59%
“…However, swell amplitudes are typically much greater than infragravity wave amplitudes, such that the benchmark model predicts they create strains of comparable magnitude (Bennetts, Liang & Pitt 2022). In particular, flexural-gravity waves at periods in the swell regime are amplified by crevasses in ice shelves (Bennetts et al 2022), and, thus, our findings highlight a potential, additional role of water-ice coupling and extensional waves in these amplifications. Further, the thin-plate model presented could be extended to study whether periodic thickness variations in the ice shelf block ocean wave energy propagation through the shelf (Freed-Brown et al 2012;Nekrasov & MacAyeal 2023).…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Ice shelf flexure has been detected in response to swell ( § 5.1), as well as tides ( § 5.2), infragravity waves and tsunamis (Bromirski et al, 2010;Brunt et al, 2011;Padman et al, 2018). Flexure due to swell is greatest in the outer shelf margins (Chen et al, 2018;Bennetts, Liang, & Pitt, 2022) and during summer when the sea ice barrier is at its weakest or absent (Massom et al, 2018;Chen et al, 2019). Swellinduced shelf stresses peak at crevasses (Bennetts, Liang, & Pitt, 2022), and they have been associated with crevasse and rift propagation (Banwell et al, 2017;Lipovsky, 2018), iceberg calving (MacAyeal et al, 2006;Cathles IV et al, 2009) and triggering catastrophic ice shelf disintegration events (Massom et al, 2018).…”
Section: Iceberg Calvingmentioning
confidence: 99%
“…Observation using a satellite radar altimeter for 18 years has shown that losses in the West Antarctic increased by approximately 70% in the past decade [4]. Strong evidence suggests that ocean waves contribute to the calving process of the ice shelf [5][6][7][8]. Seismic instruments have measured the impact of ocean swells on the Ross Ice Shelf in Antarctica, which causes it to vibrate [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%